The left hand of darkness - Le Guin, Ursula K., 1929- (New York : Ace Books, 2010)
An official from an interplanetary federation is called in to arbitrate peace on a planet whose inhabitants are technically advanced, androgynous, and have telepathic powers.
Booklist.
Notable/Best Books (A.L.A.).
Wilson's Senior High School.
Young Adult
Keywords: Life on other planets -- Fiction; Life on other planets -- Fiction; Science fiction